Transcriptional machineries in jasmonate-elicited plant secondary metabolism - De Geyter, Nathan; Gholami, Azra; Goormachtig, Sofie; Goossens, Alain (Trends in plant science, 2012)
Jasmonates (JAs) act as conserved elicitors of plant secondary metabolism. JA perception triggers extensive transcriptional reprogramming leading to the concerted activation of entire metabolic pathways. This observation inspired numerous quests for ‘master’ regulators capable of enhancing the production of specific sets of valuable plant metabolites. Many transcription factors (TFs), often JA-activated themselves, with a role in the JA-modulated regulation of metabolism were discovered. At the same time, it became clear that metabolic reprogramming is subject to complex control mechanisms integrated in robust cellular networks. In this review, we discuss current knowledge of the effect of JA-modulated TFs in the elicitation of secondary metabolism in the model plant Arabidopsis (Arabidopsis thaliana) and a range of medicinal plant species with structurally divergent secondary metabolites. We draw parallels with the regulation of secondary metabolism in fungi and consider the remaining challenges to map and exploit the transcriptional machineries that drive JA-mediated elicitation of plant secondary metabolism.